Directions for Improving the Quality of Accounting Information on Financial Results - Ovlayev Sukhrob Temur ugli; Mavlonova Dilrabo Uktamovna (Research Parks Publishers, 2022)
In this article discusses the requirements for the quality of accounting information. The factors influencing the formation of accounting information in the preparation of financial statements have also been clarified. As a result of the study, the directions for improving the quality of accounting information were recommended.